From Normative Authority to Contextual Responsiveness: Theoretical and Empirical Analysis of DSN–MUI’s Transformation in Fatwa Formulation within Indonesia’s Islamic Finance Ecosystem - Hidayah, Nur; Haryatih, Haryatih; Solihah, Ucu (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
This study examines how the National Sharia Council of the Indonesian Council of Ulama (DSN–MUI) formulates and adapts fatwas amid increasing complexity in Islamic economic practice, addressing the problem of tension between classical fiqh normativity and contemporary transactional demands where explicit naṣṣ and ijmāʿ are limited. Specifically, the research asks: (1) how does DSN–MUI reconcile traditional Sharīʿah principles with novel financial needs; (2) what juristic tools and maxims inform its fatwa-making; and (3) what are the practical consequences for Islamic financial institutions (LKS) and consumers. Employing a qualitative doctrinal and socio-legal method, the study analyzes selected DSN–MUI fatwas focusing on the transformation of tabarruʿ contracts (wakālah, ḥawālah, kafālah) into tijārī frameworks and the evolving rulings on muqāṣah (early-payment discounts) in murābaḥah as primary data. The findings reveal a clear methodological shift from a strictly textual-normative approach toward a contextual, maqāṣid- and maṣlaḥah-oriented reasoning that treats al-ashlu fil muʿāmalāt al-ibāḥah as a governing hermeneutic; DSN–MUI legitimizes innovations (e.g., wakālah bi al-ujrah, ḥawālah bi al-ujrah, kafālah bi al-ujrah, and obligatory muqāṣah) while embedding procedural safeguards (pre-agreed nominal ujrah, protections against ribā, gharar, and ziyādah ʿalā al-dayn) to protect consumers. The study concludes that DSN–MUI functions as an adaptive Sharīʿah governance actor that balances normative fidelity, institutional viability, and public interest, recommending continued doctrinal clarity and empirical assessment of socio-economic impacts.